Hubungan Indeks Massa Tubuh Ibu Dengan Kejadian Bayi Berat Lahir Rendah di RSUD Wonosari Gunungkidul - Fatinah, Mutiara; Theresia, Endah Marianingsih; Wahyuningsih, Heni Puji (Jurnal Kesehatan Ibu dan Anak, 2017)
Low birthweight is a baby who is born weighing less than <2500 gram. Low birthweight is one of the most causes of the neonatalmorbidity and mortality in Indonesia. The highest incidence of low birthweight in DIY province was happened in Gunung Kidul district(7.33%). Low birthweight is caused by many factors such as the mother's nutrition status. Body Mass Index (BMI) is one ofindicators to measure the nutrition status on adults. In Indonesia, the ideal body weight of a woman during her first trisemester is 45-65 kg, while mother's weight >45 kg can possibly have low BMI. The objective of this study is to know the correlation between thebody mass index of mothers and the incidence of low birthweight. The design of this study used case control. Total sample was 326newborn babies which consisted of 163 babies in the case group and 163 babies in the control group who had fulfilled the inclusiveand exclusive criteria. The data was collected from the medical records since January-December 2015 with purposive samplingtechnique. The data analysis used chi-square, OR and logistic regression. The result of bivariat analysis showed the variableswhich were correlated with the incidence of low birthweight i.e. BMI of mothers (p=0.000, OR: 2.4), age (p=0.028, OR: 1.6) andanemia TM III (p=0.017, OR: 1.7), while the parity variable was not correlated with the incidence of low birthweight (p=0.0912, OR:1.02). The result of multivariate analysis showed that BMI of mothers was the most correlated variable with the incidence of lowbirthweight (p=0.000, OR: 2.8). Mothers with low BMI was 2,8 times at risk of having babies with low birthweight than mothers withnormal BMI. This study concluded that there was a correlation between mothers' BMI, age and anemia TM 3 with the incidence oflow birthweight. Low BMI was the most risked variable for mothers to bear babies with low birthweight. Low BMI increased theincidence of low birthweight.